New techniques for statistical quality control - Wang, Zhigang. (2008)
This thesis investigates several new techniques in attribute Statistical Quality Control (SQC). Two optimal Rectifying Sampling Plans (RSP) are proposed first and are illustrated with implementation examples. One optimum rectifying inspection algorithm minimizes the Average Total Inspection (ATI), and the other minimizes the Average Outgoing Quality (AOQ).